ANALISIS STRATEGI PEMASARAN DALAM UPAYA PENINGKATAN PANGSA PASAR PERUSAHAAN STUDI KASUS : GRAND SWISS-BELHOTEL MEDAN - JOHANES WILFRID PANGIHUTAN PURBA (JURNAL ILMIAH SIMANTEK, 2019)
Grand Swiss-Belhotel Medan is one of the five-star business hotels in the city of Medan, which started operations on September 23, 2008 with 242 rooms under Swiss-Belhotel International management. Grand Swiss-Belhotel Medan in 2009-2010 ranks second from the average five-star hotel market share in the city of Medan at 23.49% of the total market. The first room occupancy rate was 71.25% in 2012. In this situation new competitors will emerge, competition is expected to increase, especially in efforts to maintain, compete and seize the existing market share to become the market leader. The purpose of this study is to evaluate the marketing strategies that have been implemented effectively to increase the market share of Grand Swiss-Belhotel Medan. To achieve these objectives, a case study research approach is supported by a survey of 100 Grand Swiss-Belhotel Medan guests with a simple random sampling method. The research method used is a qualitative method presented descriptively and the analysis tool used consists of, the input stage with the Internal Factor Evaluation (IFE) matrix and the External Factor Evaluation (EFE) matrix, the matching stage with the SWOT matrix and the decision stage using the Quantitative matrix Strategic Planning Matrix (QSPM). The results showed that the promotion factor had a less dominant level of room occupancy at 2.68. Analysis of external and internal factors using the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices indicate that external influences are greater than those of internal factors.